If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -1(x + -2) = -36 + -1(4 + -1x) Reorder the terms: -4x + -1(-2 + x) = -36 + -1(4 + -1x) -4x + (-2 * -1 + x * -1) = -36 + -1(4 + -1x) -4x + (2 + -1x) = -36 + -1(4 + -1x) Reorder the terms: 2 + -4x + -1x = -36 + -1(4 + -1x) Combine like terms: -4x + -1x = -5x 2 + -5x = -36 + -1(4 + -1x) 2 + -5x = -36 + (4 * -1 + -1x * -1) 2 + -5x = -36 + (-4 + 1x) Combine like terms: -36 + -4 = -40 2 + -5x = -40 + 1x Solving 2 + -5x = -40 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + -5x + -1x = -40 + 1x + -1x Combine like terms: -5x + -1x = -6x 2 + -6x = -40 + 1x + -1x Combine like terms: 1x + -1x = 0 2 + -6x = -40 + 0 2 + -6x = -40 Add '-2' to each side of the equation. 2 + -2 + -6x = -40 + -2 Combine like terms: 2 + -2 = 0 0 + -6x = -40 + -2 -6x = -40 + -2 Combine like terms: -40 + -2 = -42 -6x = -42 Divide each side by '-6'. x = 7 Simplifying x = 7
| 12/8=30/n | | -3(4x-4)=6(3x-4)+156 | | 5(x+5)-4=1(x+2) | | 8t-22=-8t | | v/5=5 | | 10y-1y+7=-2y+62 | | 5y-10y+6=4y-12 | | 2t+4+9t=4t-17 | | 7z-11-z+5= | | 73+79+x=180 | | 3.8x+5.4=4.4x+2.4 | | 6.9t+2.4=-5.2t-33.9 | | .5x-34=.583x+14 | | 4t+3=7t-9 | | 5x^2-25x+21=1 | | 2.5y=3.1y-1.8 | | x-x/2-x/3=-1 | | -4a+5=3a+19 | | 4x^2-24x+21=1 | | 3x+5y-x+2y=0 | | 5/6*3/10 | | 3x/4a*8a^4x^3/9x | | -3x+6=-2x+2 | | ((4x^4y^2)/(6xy))^2 | | s=5(3.14)sh+5(3.14)squared | | -.25x=9-.666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666x | | x+2x^2+1=-1-x | | 5x-81=15+2x | | 105+3x=8x | | 50x^2+3x-1.5=0 | | .4x-15=.625x-16 | | (32x-8)/3x=10 |